Electrospun PVA/CQD nanofiber–coated carbon anode for high–performance microbial fuel cells: A comparative study - Firman Ridwan; Muhammad Restu Raimon; Dean Bilalwa Agusto; Wismalqi Wismalqi; Feskaharny Alamsjah (International Journal of Renewable Energy Development, 2026)
This study details the development of a high-performance microbial fuel cell (MFC) utilizing a nanofiber-coated carbon anode, fabricated through the electrospinning of polyvinyl alcohol (PVA) integrated with carbon quantum dots (CQDs). A dual-chamber H-type MFC, with a working volume of 50 mL for both anode and cathode compartments, was operated in batch mode using sterilized sugarcane juice, adjusted to a pH of 7.0, as the organic substrate. Two electrogenic bacteria, Bacillus subtilis and Escherichia coli, were separately immobilized within the PVA/CQD nanofiber matrix to assess their electrochemical performance. Structural and chemical characterizations using SEM, FTIR, and UV–Vis spectroscopy confirmed the successful incorporation of CQDs and effective bacterial colonization within the nanofiber network. Electrochemical studies, such as CV and EIS, indicated low charge transfer resistance and improved electron kinetics especially when B. subtilis was present and an Rct of about 400 ohms. MFCs based on B. subtilis reached a maximum power density of 1754 mW/m² on day four of operation at a fixed external resistance of 100 0 and the electrode surface area of 9.45 cm², about 3.5 times greater than the power density obtained with E. coli (491 mW/m²). This has been due to the high performance of B. subtilis which can form a robust conductive biofilm, releases endogenous redox mediators, and has the ability to metabolize sugar rich substrates efficiently. These findings underscore the potential of PVA/CQD nanofiber-coated carbon anodes as an effective strategy for enhancing MFC performance and provide a promising foundation for future optimization and scale-up toward sustainable energy generation from organic waste at the laboratory level.